Analytical Study on Growth and Performance of Agricultural Exports of India: Examining the Success and Trends of Agricultural Exports in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Considering the country's conducive climate for food production and the ever-increasingdemand for processed food items, India's food processing industry (FPI) is sometimes referred to as thedawn sector owing to its enormous potential for growth and development. When compared to the entireGVA produced by the economy in 2018–19, this industry accounted for around 1.62 percent. In fact, itaccounts for 14.28 of the country's overall job output across all industries. Since the FPI in India is sofocused on international trade, this research will analyze the success of Indian processed food exports.The research was conducted by relying on secondary resources, such as yearly reports from variousgovernment agencies and non-profits. The largest rates of expansion for exports to these markets wereseen in Indonesia (102.42 percent), Bangladesh (94.9 percent), and Nepal (50.4 percent). The agriculturalindustry of India mainly exports agricultural goods, maritime goods, plantation goods, and agriculturalbyproducts including textiles and food. The value of exports of agricultural and associated goodsincreased by 17 to 37.3 billion in 2020–21.